2017
DOI: 10.3390/en10070938
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Copper Particles on Breakdown Voltage and Frequency-Dependent Dielectric Property of Vegetable Insulating Oil

Abstract: Abstract:The insulating performance of oil is vulnerable to particles especially the conductive particles. This paper investigated the influence of copper particles of micrometer size on the breakdown strength and frequency-dependent properties of vegetable oil. The AC breakdown voltage of contaminated vegetable oil with copper particles of different numbers (ranging from 10 3 to 10 6 ) was measured. The frequency-dependent dielectric properties including volume resistivity, relative permittivity and dissipati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Therefore, it will trap the passing electrons and consequently lead to an enhancement of dielectric strength [11]. In spite of this, it has been reported that the addition of conductive nanoparticles in a certain amount reduces the dielectric strength of base oil [12][13][14]. When the number of nanoparticles is increased, the collision rate between the particles increases due to Brownian motion, but it appears as bridging between two conductors and could lead to breakdown [15].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it will trap the passing electrons and consequently lead to an enhancement of dielectric strength [11]. In spite of this, it has been reported that the addition of conductive nanoparticles in a certain amount reduces the dielectric strength of base oil [12][13][14]. When the number of nanoparticles is increased, the collision rate between the particles increases due to Brownian motion, but it appears as bridging between two conductors and could lead to breakdown [15].…”
Section: Introductionmentioning
confidence: 99%
“…However, the nonconductive magnetic nanoparticles are able to convert such fast-moving electrons into slow-moving negatively charged particles [16]. Some researchers studied that the addition of conductive nanoparticles such as oxonickel (Fe 2 NiO 4 ), ferric oxide (Fe 2 O 3 ), and copper at a certain amount of concentrations may reduce the dielectric strength of insulating oil [6,[17][18][19][20]. While zinc oxide (ZnO) [21] and copper oxide (CuO) [22] are categorized as classical semiconductive nanoparticles that are often used by researchers worldwide, they are also trusted as the main contributor to the enhancement of transformer oil performance [23,24].…”
Section: Nanomaterialsmentioning
confidence: 99%
“…The presence of conductive particles always leads to the reduction of breakdown voltage of insulating liquid. As the particle's size and concentration increase, the insulating performance is further inhibited [65][66][67]. According to available researches up to now, it seems that the particle acts as 'weak point' to initiate a breakdown, but has no immediate effect on the breakdown process, e.g.…”
Section: Breakdown Related To Conductive Particlesmentioning
confidence: 99%